Screening of Rice Genotypes Based on Root Growth for Salt Tolerance at Germination Stage - Jharna, DE; Hossain, MA; Chowdhury, BLD; Lita, MAA; Islam, MM (Journal of Environmental Science and Natural Resources, 2017)
Salinity induced changes in root length and weight under salt tolerant condition. To examine the effect of different degrees of salinity on the root growth of rice, a total of 127 rice genotypes including mostly traditional, cultivated in the coastal regions of Bangladesh and some improved genotypes were used in the study. The study was conducted in petri dish providing 0, 6, 9, 12 and 15 dS m-1 (deci Siemens) salinity. Based on the performances, genotypes were scored and grouped as highly tolerant (score 1), tolerant (score 3), moderately tolerant (score 5), susceptible (score 7) and highly susceptible (score 9). Salinity stress reduced the root length and weight of rice genotypes. But the extent of root length and weight, varied with genotypes and levels of salinity. Generally in control condition root length and weight was found higher and it gradually decreased with increasing salt concentration. Based on decrease of root dry weight at 15 dS m-1 salinity, 8 genotypes scored 1, 28 scored 3, 40 scored 5, 35 scored 7, and 16 scored 9. Regarding root length, 14 genotypes were found highly tolerant, 18 were tolerant, 27 moderately tolerant, 38 susceptible and 30 were highly susceptible. Based on the score, the relationship between salinity level and tolerances of the different rice genotypes can be understood. J. Environ. Sci. & Natural Resources, 10(1): 45-53 2017